The Art and Science of Valuing in Psychotherapy : Helping Clients Discover, Explore, and Commit to Valued Action Using Acceptance and Commitment Thera. - Dahl, JoAnne, 1951- (New Harbinger Publications, 2009)
The Art and Science of Valuing in Psychotherapy shows therapists how to help their clients discover and commit to their core values, a key process in acceptance and commitment therapy (ACT). The book also presents the theory and research behind valuing in psychotherapy.